Analisis Keprofesionalisme Guru BK dalam Menghadapi Masalah Siswa - Harahap, Akhir Pardamean; Hasibuan, Nurmina Wati; Adela, Nurul; Nurhaliza, Nurhaliza; Saragih, Yulia Erwina (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Aims to determine the professionalism of BK teachers in dealing with student problems. This research uses a type of library research method. This library research is carried out by collecting various reading references that are relevant to the problem being researched, then understanding it carefully and carefully so as to obtain research findings. Research results: Professional competency in the Minister of National Education Regulation Number 27 of 2008 includes a guidance and counseling teacher who masters the concepts and practice of assessment to understand the conditions, needs and problems of clients; master the theoretical and practical framework of guidance and counseling; designing guidance and counseling programs; implement a comprehensive guidance and counseling program; assess the process and results of guidance and counseling activities; have awareness and commitment to professional ethics; master the concepts and practice of research in guidance and counseling. Key words: professionalism, guidance and counseling teachers, student problems